2020
DOI: 10.3390/app10134493
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis and TiO2 Photocatalytic Treatment under UVC/VUV Irradiation for Simultaneous Degradation of Pesticides and Microorganisms

Abstract: Efficiencies of various treatments for UVC photolysis (ultraviolet light-C at 254 nm), VUV photolysis (vacuum ultraviolet light at 254 nm and 185 nm), UVC-assisted titanium dioxide photocatalysis (UVC-TiO2), and VUV-assisted titanium dioxide photocatalysis (VUV-TiO2) were investigated for the degradation of pesticides including pyraclostrobin, boscalid, fludioxonil, and azoxystrobin and inactivation of microorganisms Escherichia coli K12 as a surrogate for E. coli O157:H7 and Saccharomyces cerevisiae i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 62 publications
0
6
0
1
Order By: Relevance
“…UV light may be readily paired with ultrasound, ozone, catalysts like titanium dioxide (TiO 2 ), or hydrogen peroxide (H 2 O 2 ) to achieve stimulatory activity and has been intensively investigated for treating wastewater (Abramović et al, 2012). Pesticide residues from fresh-cut carrot surfaces were efficiently removed with the combined UV-TiO 2 (Choi et al, 2020). Indirect photochemical processes (e.g., UV radiation in the presence of oxidants (H 2 O 2 ), catalysts elements such as ferric ion (Fe 3+ ) or H 2 O 2 /ferrous ion (Fe 2+ ), zinc oxide, TiO 2 , cadmium sulfide (Swarnam & Velmurugan, 2013), or treatment emitting more vigorous intensity of light all can enhance degradation rate like pulsed light technology.…”
Section: Effect Of Modified and Combined Uv Light Applications On Pes...mentioning
confidence: 99%
“…UV light may be readily paired with ultrasound, ozone, catalysts like titanium dioxide (TiO 2 ), or hydrogen peroxide (H 2 O 2 ) to achieve stimulatory activity and has been intensively investigated for treating wastewater (Abramović et al, 2012). Pesticide residues from fresh-cut carrot surfaces were efficiently removed with the combined UV-TiO 2 (Choi et al, 2020). Indirect photochemical processes (e.g., UV radiation in the presence of oxidants (H 2 O 2 ), catalysts elements such as ferric ion (Fe 3+ ) or H 2 O 2 /ferrous ion (Fe 2+ ), zinc oxide, TiO 2 , cadmium sulfide (Swarnam & Velmurugan, 2013), or treatment emitting more vigorous intensity of light all can enhance degradation rate like pulsed light technology.…”
Section: Effect Of Modified and Combined Uv Light Applications On Pes...mentioning
confidence: 99%
“…The effect of UV light sources on the degradation of pesticides was further investigated, including VUV, and UVC. Results demonstrated that VUV (185 nm) was more effective than UVC (254 nm) in the degradation of pesticides such as pyraclostrobin, boscalid, fludioxonil, and azoxystrobin under the same reaction condition ( 53 ). It was mainly due to VUV at 185 nm could produce more energetic photons.…”
Section: Applications Of Photolysis During Food Processingmentioning
confidence: 99%
“…Thus, its effective removal from aqueous phases has attracted scientific interest. Among different AOPs, heterogeneous photocatalysis has been evaluated for the removal of boscalid from aqueous matrices using mainly TiO 2 -based and ZnO catalysts [27][28][29][30][31][32]. Despite significant advancements in photocatalysis research in recent years, the effectiveness of this process in the removal of boscalid using alternative photocatalysts remains limited.…”
Section: Introductionmentioning
confidence: 99%